Variation in forensic DNA profiling success among sampled items and collection methods: a Queensland perspective - Krosch, Matt N. (Australian journal of forensic sciences, 2021)
Understanding the relative success of recovering DNA profiles from different touched evidentiary items/substrates, and between different methods of collection, is critical for optimal targeting of forensic sample collection and triaging for analysis. Further, reporting of such success statistics allows comparison between jurisdictions that can drive improvements and prompt discussion between stakeholders. This study analysed success statistics for DNA sampling from major and volume crimes attended by the Queensland Police Service, Australia, from February 2018 to September 2019. In total, 36416 total records were analysed, representing the most comprehensive analysis of its kind to date. Percentage successes were determined for various sample types and items, including those that are commonly encountered or have high probative value. Results suggested that, overall, around 9.5% of trace DNA samples returned full profiles, but with some disparity between swabs (13.48%) and tapelifts (6.02%). Nevertheless, trace DNA samples contributed nearly 40% of total suspect identifications (tapelifts 20.05%; swabs 18.76%). Substantial variation in profiling success among items/substrates was observed, as there was between swabs and tapelifts taken from the same item. These data contribute significantly to our understanding of DNA prevalence and recovery and provide a critical evidence base to inform changes to operational procedures.